2016
DOI: 10.1016/j.bcp.2016.01.020
|View full text |Cite
|
Sign up to set email alerts
|

Prenylated quinolinecarboxylic acid derivative suppresses immune response through inhibition of PAK2

Abstract: Development of new immunosuppressing agents is necessary in organ transplantation or immune diseases. Because Ppc-1 exhibits a suppressing effect on interleukin-2 (IL2) production in Jurkat cells, we synthesized and screened Ppc-1 derivatives that preserve prenylated quinolinecarboxylic acid (PQA) structure, and identified compound 18 (PQA-18) as a novel molecule with immunosuppressing effect. PQA-18 suppressed not only IL2 but also IL4, IL6, and tumor necrosis factor-α production in human peripheral lymphocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Molecular basis of LRRK2 inhibition by PQA-11 remains to be solved. On the other hand, we have previously reported that another PQA compound, PQA-18, suppresses PAK2 activity [24]. PAK is a kinase regulated by p21…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular basis of LRRK2 inhibition by PQA-11 remains to be solved. On the other hand, we have previously reported that another PQA compound, PQA-18, suppresses PAK2 activity [24]. PAK is a kinase regulated by p21…”
Section: Discussionmentioning
confidence: 99%
“…The PQA compounds used in this study were synthesized and purified as previously described [23,24], and the structure and purity were confirmed by 1 H and 13 C NMR spectroscopy and high-resolution mass spectroscopy. The purities of all compounds were greater than 98%.…”
Section: Antibodies and Chemicalsmentioning
confidence: 99%
“…Prenylation of the latter with prenyl bromide under basic conditions gave Ppc‐1 ( 28 ). Ppc‐1 was shown to be a mitochrondrial uncoupler and derivatives of Ppc‐1 were shown to suppress production of interleukin‐2, an immunoregulatory protein, in Jurkat cells …”
Section: Substituted Phenyl Compoundsmentioning
confidence: 99%
“…The naturalproducts Pt-1-5 (23)(24)(25)(26)(27)were obtained from methanolic extractso ff ruiting bodies of P. tenuissimum;P pc-1 (28) was obtained analogously from fruiting bodies of P. pseudocandidum (Scheme 4). [22] To confirm the structure determined by NMR studies, Pt-4 (26)w as synthesized from 5-methoxyresorcinol (29)( Scheme 4b); installation of the acyl side chain was achieved by Friedel-Crafts acylation with butanoyl chloride.…”
Section: Dictyoquinonementioning
confidence: 99%
See 1 more Smart Citation